Acute multisystemic thromboembolism manifesting as cerebral infarction, myocardial injury, and quadriparesis: a novel triad of idiopathic hypereosinophilic syndrome - Bai, Yong; Shang, Ruiling; Liao, Minglang; Sun, Yanrong (Frontiers in Medicine, 2025)
BackgroundHypersegmented Eosinophil Syndrome (HES) is a rare myeloproliferative condition with several clinical symptoms. Idiopathic HES presenting with acute, contemporaneous multisystem thrombotic episodes is extremely unusual, making clinical detection difficult and increasing the risk of misdiagnosis.Case presentationThis paper describes the case of a 69-years-old male patient with a history of coronary heart disease and hypertension, who was admitted for “dizziness accompanied by discomfort in the left shoulder and precordial region.” The patient was initially diagnosed with posterior circulation ischemia, but quickly developed a clinical trial of acute cerebral infarction (confirmed by cranial MRI), non-ST-segment elevation myocardial infarction (confirmed by progressively rising cardiac markers and ECG), and acute quadriplegia (muscle strength 0–3). Laboratory tests revealed significant peripheral blood eosinophilia (43.4%). Coronary CT scans ruled out acute in-stent restenosis. Bone marrow aspiration and genetic testing ruled out other clonal anomalies, resulting in a diagnosis of “idiopathic hypereosinophilic syndrome.”DiscussionThis case report describes a novel clinical situation in which an acute thromboembolic triad (cerebral infarction, cardiac damage, and quadriplegia) is the first presentation of idiopathic HES. It demonstrates that eosinophil-mediated hypercoagulability is the primary pathogenic mechanism behind multisystem embolism.ConclusionPrompt blood tests to assess eosinophil counts remain critical for early identification of HES, especially in the absence of usual clinical history. Early and strong glucocorticoid treatment efficiently reduces eosinophil levels and improves prognosis.